THE SEMANTIC AND CONTEXTUAL ASSESMENT OF CLICHÉ WORDS IN THE COURSE BOOK “TURKISH TEACHING SET FOR FOREIGNERS” - Yılmaz, Gülşen (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
Language is a complex structure containing the codes of a nation’s lifestyle, economy, geography and various values, which was formed by humanity in unknown periods within the framework of the law of linguistic arbitrariness. This structure also involves the culture of the nation in which it was born. Therefore, learning and knowing a language means having a grasp of the culture in which that language is used. Thus, it can be said that language teaching is an important element of cultural transmission. Indirect transmission of culture to the learner in language teaching is possible through syntax, semantics, phonetics and morphology, in addition to the consideration of the usage value of words in sentences, teaching words with a high frequency of use, and most importantly teaching the vocabulary of language. Vocabulary is one of the most significant factors reflecting the traditions and customs, social structure, lifestyle, habits, world view and numerous other characteristics of those who use that language. There is more than one category within vocabulary, such as nouns, adjectives, pronouns and adverbs. On the other hand, there are also cultural structures usually used in word groups in a formulaic way, which can probably be understood only by the users of the language they belong to, such as idioms, proverbs, reduplicated words and cliché words. For this reason, these structures play an important role in teaching language to foreigners and they are paid great attention in foreign language teaching. This study aims to evaluate the use of cliché words with different numbers of words in the A1 level course book “Turkish Teaching Set for Foreigners” by Gazi University, TOMER, their semantic and contextual assessment and their suitability for the level and to draw a conclusion by taking into consideration the assessment and classification of “meaning and context” about cliché words by Gökdayı.